Associations between music and the sensory system: An integrative review for child therapy. (July 2019) - Simhon, Vered; Elefant, Cochavit; Orkibi, Hod
Highlights: Sensory processing disorder includes a developmental lag, behavioral and emotional problems. Music and the sensory system (SS) are both linked to the nervous system. The link of music and SS was examined in 17 published articles published 1985–2017. We found two main links: music-sensory system and sensation seeking-features of music. Music may improve SS plasticity, self-confidence, communication and social skills. Abstract: Sensory processing disorder (SPD) is a disruption in the organization of sensory input that affects appropriate responses to the demands of the environment. The consequences of SPD in children may include a developmental lag as well as behavioral and emotional problems. Music therapy is particularly suitable for children with a sensory processing disorder because music and the sensory system are both linked to the nervous system. This suggests there is a need to better understand the relationship between the sensory system and the characteristics of music. An integrative review method was chosen here, given the small number of published articles on music and SPD. This integrative review covers 17 articles published between 1985 and 2017. A search was carried out in five major databases, eight music therapy journals, and grey literature. To assess the quality of a study, the Cochrane Collaboration tool for assessing risk of bias was used when possible. The results point to two types of associations: between music and the sensory system, and between sensation-seeking and features of music. Studies have also shown that therapeutic listening programs improved the sensory profiles of children with SPD. These findings lead to the practical conclusion that music is a suitable therapy for children with SPD. The benefits include improvement in the plasticity of the sensory system, motivation, self-confidence, communication and social skills.